(untitled) (World Bulletin of Social Sciences, 2023)
In 2012, it was exactly 100 years since the preparation and publication of the book by a prominent scientist, an active member of the Orenburg Department of the Russian Geographical Society and a member of the Orenburg Scientific Archival Commission, A.I. Dobrosmyslov, author of the book “Tashkent in the Past and Present”. The book consists of 15 chapters and covers the following issues: About the history of the city before the conquest, historical facts related to the conquest of the city, the organization of administration of the region with the capital in the city of Tashkent, Economic Administration and courts of the indigenous population, city self-government, income and expenses of the city, urban improvement, educational institutions, societies and institutions promoting education, libraries and museums and book trade, press, printing and lithographs, learned societies, scientific institutions, statistical committees and societies promoting the dissemination of useful knowledge, Orthodox churches, churches of heterodox Christian denominations, synagogues and mosques, medical and sanitary part and veterinary supervision, trade and industry, charitable institutions and various kinds of societies, government and public institutions, various events not included in any of the previous chapters